Business Model Canvas : Automatic Dishwasher / Samihah Mohamad Yusoff - Mohamad Yusoff, Samihah (2020)
The Automatic Dishwasher designed to solve the customer problem that face problem to clean the dishes so we created Automatic Sponge that will move automatically so customers do not have to clean dishes manually. Automatic Dishwasher has Adjustable Button that will manage customers to adjust the speed so it is also user friendly. Sponge’s size improves to more thick so the dishes will be more clean. Place to refill detergent will enable user to clean dishes anywhere and anytime